Hubungan Durasi Paparan Gelombang Elektromagnetik Telepon Seluler Terhadap Kadar Melatonin Pada Tikus Putih (Rattus norvegicus) Galur Wistar - Putri, Irrayanti; Harliansyah, Harliansyah (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2018)
Background : Mobile Phone (MP) is a wireless communication tools that nowadays used by people with many features that can ease the user. Cellphone is releasing electromagnetic radiation that can causes side effect for the user itself, one example of the side effect is disturbing the melatonin hormone synthesis that can cause the abnormal sirkadian body rythm, so the sleep patterns are disrupted, causing insomnia, islam is teaching us to keep our health, for example is to keep the rythm of our bedtime regularly. Objective : Knowing the relation between exposure duration of mobile phone electromagnetic radiation to melatonin level of Wistar albino rats observed by medicine and islam perspectives. Methods : This study was experimental study, total sample was determined by frederer theory and analyzed using IBM SPSS Statistic 21 for Windows. Results : The results showed that melatonin levels in the positive control group (dark control group) 13,705 ± 0,500 were compared with the group which exposed for 3 hours 13,375 ± 0,654 with (p=0,299) and in the positive control group (dark control group) 13,705 ± 0,500 compared with the group which exposed for 6 hours 13,223 ± 0,529 with (p=0,116). Conclusions : There is no significant relation between exposure duration of mobile phone electromagnetic radiation to melatonin levels in Wistar albino rats.